Pengembangan E-Modul Dalam Pembelajaran Seni Dan Budaya Di Madrasah Ibtidaiyah: Pengembangan E-Modul pada Pembelajaran Seni Budaya di Madrasah Ibtidaiyah - Yandi; Putra, Chandra Anugrah; Suriansyah (CV Aisha Edutama, 2025)
According to the needs analysis, teachers have not fully utilized technology-based media and teaching materials. Teachers have not fully produced technology-based media and teaching materials. This research aims to produce simple e-module teaching materials for learning art and culture. This research method uses the example of ADDIE research and development. The results of the study show that the e-module is developed through needs analysis, prototype design, prototype development, field tests, and product assessment. This study shows that simple e-modules are used in learning using a score of 86.5%. The level of independence of the e-module that can be accepted is shown using the eligibility criteria achieved by the student through integrated material support using web-based learning links. According to expert validation, this e-module is suitable to be used as a teaching material for learning art and culture based on personal computers in grade IV of Madrasah Ibtidaiyah.